Violência em relacionamentos íntimos entre homens - Martins, Joyce Hellem Delmiro (2019)
Violence in intimate relationships (VRI) is one of the major problems in our country. Nonetheless, the media and the social imagery highlight only cases associated with women in heterosexual relationships, that is, little is said about how violence can be expressed in dating, engagement or marriage between two men or two women. Based on this assumption, this dissertation aims to understand the violence between men in intimate relationships. It is based on a psycho-sociological view that has as main theoretical ground the Pierre Bordieu’s gender perspective, Ayres’s perspective on Vulnerability of and Moscovici’s Social Representations Theory. It is structured in three complementary articles/ researches in its objectives. The first article aimed to investigate the representational contents of the media about violence between men in intimate relationship. A survey was carried out based on the search of electronic newspapers, published in Portuguese, between 2008 and 2018. After selection through exclusion criteria, 32 articles were analyzed. From the Descending Hierarchical Classification (CHD) and Factorial Correspondence Analysis (AFC), five discursive Classes emerged in which, in general, the presence of a discourse mainly directed to the most extreme forms of violence, delegating the more subtle and psychological aspects of the phenomenon to the background. In addition, the underreporting of the phenomenon is confirmed. The second article aimed to investigate how much the predictive variable (PV) Internalized Heterosexism is associated with the criterion variable (VC) Violence between Men’s couples. The Revised Conflict Tactics Resolution Scale (CTS2) and the Internalized Homophobia Scale (IH) were used, as well as a sociodemographic questionnaire. The sample consisted of thirty men who are currently or at least once were in a relationship with another man, ranging in age from 20 to 50 years old (M = 27.25, SD = 7.5). We analyzed the scores of the participants in the CTS2 scale to obtain data on the prevalence of different conflict tactics. It was observed that the most used tactic by participants in conflict resolution is Negotiation (M = 18.73, SD = 6.02), followed by Psychological Aggression (M = 12.44, SD = 5.87). Participants tended to score high on the subscale Public Identification as a Gay Man (M = 32.74, SD = 8.93). There was no association between the scales, which can be credited to the small sample size. Thus, this study does not allow us to verify whether internalized heterosexism is a predictor of violence between couples of men. However, there were associations between Public Identification as Gay and Moral Acceptability of Being Gay (rho = .636, p <0.01), Moral Acceptability and Stigma Perception (rho = .378, p <0.05) (Rho = .593, p <0.05), Psychological Aggression and Sexual Coercion (rho = .593, p <0.05) , 05) and Religiosity and Relationship Time (rho = .465, p <0.05). In general, the data indicate that violence among men is a very frequent phenomenon that can be captured even in small samples, which denounces the urgency of bringing visibility to the problem. The third article aimed to understand the experiences of men in intimate relationships with other men. Seven gay men aged 27 to 40 years (M = 32.7, SD = 4.7) were interviewed and the contents of the interviews were submitted to the content analysis proposed by Bardin, which originated five broad thematic categories: Vulnerabilities and Violence, Social Support, Consequences of the Experiences, Identity Building and Negotiation/Partnership. The analysis indicated that the experiences of men are often traversed by elements of violence of which they are either victims or perpetrators., The results obtained in this dissertation altogether point out that violence in relationships between men manifests at alarming levels and can only be understood by taking into account the specificities of affective practices that go beyond heteronormativity.